Frontotemporal dementia and progressive supranuclear palsy‐like syndrome with a novel TARDBP mutation. Issue 2 (29th February 2016) - Yabe, Ichiro; Nakano, Fumihito; Shirai, Shinichi; Matsushima, Masaaki; Takahashi, Ikuko; Sasaki, Hidenao
Abstract: TARDBP mutation has been shown to cause frontotemporal dementia and progressive supranuclear palsy‐like disease. In this case study, we present the first reported Japanese case of frontotemporal dementia and progressive supranuclear palsy‐like syndrome caused by a novel TARDBP mutation. A 63‐year‐old man was diagnosed with frontotemporal dementia and progressive supranuclear palsy‐like disease. An older brother of the patient's deceased father showed similar symptoms. Genetic analysis showed a novel TARDBP heterozygous mutation (c.715 A > G, p.I239V). This mutation is not found in databases of the 1000 genome project and Human Genomic Variation, but is identified as a pathogenic mutation by Mutation Taster. Although the hot cross bun sign as a result of frontotemporal dementia and progressive supranuclear palsy has been reported only rarely, brain magnetic resonance imaging of this patient showed the hot cross bun sign and T2‐hyperintensity of the middle cerebellar peduncles along with frontotemporal and midbrain tegmentum atrophy.